Studying the Effect of Volume Fraction Variation and Environmental in Creep Behavior of Polyester Resin Composed With Fiber E-Glass(Mat) and Carbon Black Powder Particles - Jamal, Gelass M.; Jafaar, Harith i.; Rammo, Nabil N. (Science Journal of University of Zakho, 2013)
This research presents the results obtained from investigation of creep behavior for polyester resin composited with different volume fractions of fiber E-glass(roving) and carbon black powder under 4-point flexure test at ambient and 60ºC. Flexure strength of W.R. composites show best values in comparison to particulate C.B. composites or to mixed W.R./C.B. composites.The creep strain measured up to 103 h for three different stresses namely 15,30 and 45 MPa shows that W.R. composites endures least strain of all other specimens. The 60ºC temperature has little effect on the creep strain, at this temperature the creep strain increases by about 8% for the prepared specimens. Plot of creep modulus vs. time shows that the characteristic behavior is reciprocal of creep strain. Prior immersion in water to specimens for 30 days reveal that creep strain progressively increased for all prepared composites.
Keywords: The